Exploring the complexities of nonstandard employment: the 2022-23 California Work and Health Survey. - Trupin, Laura; LaFrance, Alicia; Rhee, Nari; Iley, Trisha; Mac, Ima Varghese; Yelin, Edward (Monthly Labor Review, 2026)
This article examines the 2022–23 California Work and Health Survey (CWHS), a longitudinal study developed by the California Labor Laboratory to assess traditional and nonstandard employment arrangements among California workers and their impacts on working conditions, health, and economic status. Nonstandard employment is categorized into contingent work (jobs with predetermined end dates), alternative employment (including independent contractors, temporary agency, on-call, and contract-company workers), and app-based work (short-term jobs found via digital platforms). The CWHS found higher prevalence rates of nonstandard work compared to the 2017 Current Population Survey Contingent Worker Supplement, particularly when including secondary jobs and a 30-day employment window, with about one-third of workers engaged in alternative arrangements and 7.5 percent in app-based employment. The survey also operationalized California’s “ABC test” criteria to identify potential misclassification of independent contractors, revealing challenges in worker understanding of these criteria and indicating that over 11 percent of self-employed independent contractors may be misclassified. The CWHS highlights the complexity of measuring nonstandard employment and its implications for worker protections and well-being in California’s evolving labor market.